Educational Values in Seloko Traditional Marriage of the Mersam Community, Batanghari Regency - Irma Suryanti (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: This study aims to examine the value of education because the value of education provides extraordinary benefits for creating a living environment, and can provide the most valuable information regarding outlook on life, the future, and assist humans in preparing their essential needs to deal with change. Methodology: This research is included in the qualitative descriptive research. The instruments used in this study are based on the characteristics found in the literature review. These characteristics are grouped based on educational values: having faith in and fearing God Almighty, having a noble character, being healthy, knowledgeable, democratic, and being responsible. The data analysis technique used in this study uses the mark reading technique, namely looking directly at the markers being studied. Main Findings: In the customary marriage verses of the Mersam Community, Batanghari Regency, there are six educational values, namely the first is the value of education of faith and piety to God Almighty contained in the verses (1) Apply, (2) Order to Pick Up the Bride, (3) Open Lanse. The value of education of faith and piety to God Almighty is manifested by orders to carry out and obey His prohibitions, be grateful and pray. Novelty/Originality of this study: Assessment of wisdom values in the environment is very important to do, because by knowing the wisdom values that are around, this can be an innovation for teachers in implementing learning.